Comparison the effect of casein phosphopeptide amorphous calcium phosphate and fluoride varnish on dentin hypersensitivity reduction - Leila Pishevar; Shirin Zahra Farhad; Mahboube Mirzakhani; Navid Haghayegh; Mohammadreza Ansarinejad (Babol University of Medical Sciences, 2015)
Introduction: Nowadays, several casein components such as casein phosphopeptide amorphous calcium phosphate (CPP-ACP) are vastly considered as a suitable replacement for fluoride component . The aim of this study was to compare the effect of CPP-ACP paste and fluoride varnish on dentin hypersensitivity reduction. Materials & Methods: In this clinical trial study, thirty adult patients between the ages of 20-50 years, presenting with the chief complaint of dentin hypersensitivity were examined. The loss of dentin was less than 0.5mm. The subjects divided into three groups: In groups I and II, patients were treated using CPP-ACP and fluoride varnish following manufacturer instructions. Group III received placebo gel. A visual analog scale was used to assess subjects' response to compressed air and ice stimuli at baseline, 7 days, 28 days and 60 days after treatment. Data was analyzed by One Way Analysis of Variance (ANOVA), Duncan Post Hoc test using the SPSS software version 21. Results: The results showed significant statistical difference between the groups (P<0.05). In fluoride varnish group and CPP-ACP paste group, the dentin hypersensitivity significantly decreased when baseline scores compared to post treatment scores at 7, 28, 60 days (P<0.05). There was no significant statistical difference in dentin hypersensitivity reduction in fluoride varnish and CPP-ACP paste groups . Conclusion: The results of this study showed that both of fluoride varnish and CPP-ACP paste effectively reduced dentinal hypersensitivity compared with placebo-control group.